Duplex scanning in vascular disorders - Strandness, D. E (Lippincott Williams & Wilkins, 2002)
Univ. of Washington, Seattle. Text and reference reviews approaches to the evaluation of vascular disease and the way in which duplex scanning plays a role in that evaluation. Previous edition: c1993. Now includes the words and practice of the author\'s technologists at the University of Washington. DNLM: Vascular Diseases--ultrasonography.
Keywords: kardiovaskulární nemoci; Cardiovascular Diseases; Ultrasonography; radiologie, nukleární medicína a zobrazovací metody; ultrasonografie; kardiologie